Study of Differences in COVID-19 Vaccine Responses in Developed and Developing Countries - Winarni, Sri; Kujariningrum, Oktavia Beni; Nurhayati, Elisa; Azizah, Waviq (KEMAS: Jurnal Kesehatan Masyarakat, 2022)
SARS-CoV-2 can spread rapidly and has been shown to cause a wide spectrum of severity. Vaccines exist as a preventive effort to control the transmission of COVID-19 by forming herd immunity. The presence of the COVID-19 vaccine has caused many responses in the community, both positive and negative responses. The article aim to compare risk factors affecting people’s intentions as respond to the COVID-19 vaccine in developed and developing countries. The research was carried out in January 2021 and used the literature review method by collecting and concluding data from previous research. The search for previous research articles was carried out on the Scopus, Science Direct, Clinical Key, and SpringerLink portals with keywords in the form of COVID-19, Vaccine, Acceptance, Intention, and Hesitancy. This narrative review uses 29 articles that meet the inclusion and exclusion criteria. The intention was the lowest positive response (49.64%), and a fairly high form of doubt (71.20%) was found to be a negative response. Respondents who have high confidence in the country’s health system are at 3.05 times greater risk of having the intention to use the COVID-19 vaccine in developed countries (OR = 3.05; 1.13-4.92). Respondents over 65 years of age were at 3.65 times greater risk of having the intention to receive the COVID-19 vaccine in developing countries (OR = 3.65; 2.57-5.17). The COVID-19 vaccine creates positive and negative responses in the community. The intention is the lowest positive response influenced by trust in the country’s health system (developing countries) and age (developed countries).